Pengaruh Kualitas Produk dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Mie Gacoan Galuh Mas Karawang - Dessy Septia Azzarah; Netti Nurlenawati; Dexi Triadinda (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Nowadays, many culinary businesses have emerged with various characteristics and uniqueness, accompanied by the number of restaurants that continue to appear, which can be a threat as competition becomes increasingly fierce. This research was carried out with the aim of evaluating the impact of product and service quality on customer satisfaction at Mie Gacoan Galuh Mas Karawang. The research approach used was quantitative with Purposive Sampling, involving 96 respondents who were customers of the restaurant, selected using the Lemeshow formula. Hypothesis testing and multiple linear regression analysis to interpret data. From the research results, it is proven that product quality (X1) and service quality (X2) have a significant impact on customer satisfaction at Mie Gacoan Galuh Mas Karawang. In addition, simultaneously, (X1) and (X2) are also very significant for increasing customer satisfaction (Y). Data analysis shows that the Adjusted R Square value reached 0.763, indicating that 76.3% of the variation in customer satisfaction at Mie Gacoan Galuh Mas Karawang can be explained by the variables of product quality and service quality provided.